Mechanism of autonomous control of the Escherichia coli F plasmid: purification and characterization of the repE gene product. - Masson, L (1988)
E protein, the 29 Kd repE gene product, is essential for the replication of the Escherichia coli F plasmid. The repE gene has been cloned and expressed in an inducible ATG-fusion vector, and the protein product has been purified to homogeneity. The purified E protein is present as a dimer in solution and binds specifically to both the 19-bp direct repeats (incB) found within the mini-F origin of replication ori2 and the repE operator DNA. Examination of the amino acid sequence of E protein revealed a consensus sequence for DNA binding.